Generalized Woodall Numbers: An Investigation of Properties of Woodall and Cullen Numbers via Their Third Order Linear Recurrence Relations - Yüksel Soykan; Vedat İrge (Universal Journal of Mathematics and Applications, 2022)
In this paper, we investigate the generalized Woodall sequences and we deal with, in detail, four special cases, namely, modified Woodall, modified Cullen, Woodall and Cullen sequences. We present Binet's formulas, generating functions, Simson formulas, and the summation formulas for these sequences. Moreover, we give some identities and matrices related with these sequences.